A dual role for the lex2 locus: identification of galactosyltransferase activity in non-typeable Haemophilus influenzae strains 1124 and 2019. - Engskog, M; Yildirim, H; Li, J; Richards, J; Deadman, M; Hood, D; Schweda, E (2009)
Lipopolysaccharide (LPS) of Haemophilus influenzae comprises a conserved tri-l-glycero-d-manno-heptosyl inner-core moiety (l-alpha-d-Hepp-(1-->2)-[PEtn-->6]-l-alpha-d-Hepp-(1-->3)-[beta-d-GlcIp-(1-->4)]-l-alpha-d-Hepp-(1-->5)-alpha-Kdop) to which addition of beta-d-Glcp to O-4 of GlcI in serotype b strains is controlled by the gene lex2B. In non-typeable H. influenzae strains 1124 and 2019, however, a beta-d-Galp is linked to O-4 of GlcI. In order to test the hypothesis that the lex2 locus is involved in the expression of beta-d-Galp-(1-->4-beta-d-Glcp-(1--> from HepI, lex2B was inactivated in strains 1124 and 2019, and LPS glycoform populations from the resulting mutant strains were investigated. Detailed structural analyses using NMR techniques and electrospray-ionisation mass spectrometry (ESIMS) on O-deacylated LPS and core oligosaccharide material (OS), as well as ESIMS(n) on permethylated dephosphorylated OS, indicated both lex2B mutant strains to express only beta-d-Glcp extensions from HepI. This provides strong evidence that Lex2B functions as a galactosyltransferase adding a beta-d-Galp to O-4 of GlcI in these strains, indicating that allelic polymorphisms in the lex2B sequence direct alternative functions of the gene product.